Tanggung Jawab Pihak Ekspedisi Dalam Transaksi Pengiriman Barang - Priescillia Mariana Palapessy; Teng Berlianty; Sarah Selfina Kuahaty (PAMALI: Pattimura Magister Law Review, 2023)
Introduction: The marketplace works with the expedition as a delivery service to facilitate sellers in sending buyers' orders. The process of sending goods does not always run smoothly, there are various common problems that usually occur in the process of sending goods by the expedition. This certainly raises the distrust of service users towards the responsibility of the expedition.Purposes of the Research:  To find out the form of legal responsibility for the expedition's default and the factors that cause default by the expedition.Methods of the Research: This research uses normative research methods with the problem approach used is a statutory approach and conceptual approach, and the sources of legal materials used are primary, secondary and tertiary.Results of the Research: The results showed that if in the process of shipping goods there is a violation or negligence caused by the expedition, then the expedition as a business actor will provide compensation, this is in accordance with Article 1366 of the Civil Code. The act of default by the expedition in the delivery of goods is caused by internal and external factors that make the expedition must be responsible for the losses caused.